A review of mathematical optimization models applied to the sugarcane supply chain - Teixeira, Eduardo dos Santos [UNESP]; Rangel, Socorro [UNESP]; Florentino, Helenice de O. [UNESP]; de Araujo, Silvio Alexandre [UNESP] (Wiley, 2021)
Sugarcane is a product of great economic relevance and, as well as its use for the production of different types of sugar, it is also a renewable source for the production of bio-fuels, other bio-products, and electricity. In this context, efficient planning and technology changes are necessary to ensure high productivity, competitiveness and harmony with economic, social, and environmental issues. Consequently, this sector needs technical and scientific support. Mathematical optimization models can be useful to build efficient planning tools for the activities involved in the sugarcane supply chain, helping to address these challenges. This paper describes the sugarcane supply chain and presents a literature review of mathematical optimization models that have been proposed to represent its main stages: planting, harvesting, transporting, industrial processing, and marketing. The findings show that several models have been proposed to represent these five stages, however, most of them have not been thoroughly explored from the point of view of strength of the models and solution methods. Moreover, the harvesting stage is the one that has received more attention than the other stages. In the integration of two or more stages, there are many challenges yet to be addressed by mathematical optimization models. This review contributes to a better understanding of the sugar-energy sector and opens up new perspectives for future investigations.
Keywords: literature review; mathematical optimization models; sugar-energy sector; sugarcane; supply chain